การหาค่าพารามิเตอร์ทางชลศาสตร์ที่ใช้ในแบบจำลองทางคณิตศาสตร์ ของการตกตะกอนในร่องน้ำกรุงเทพฯ - สุธรรม วิสุทธิเมธีกร (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
This study aimed to define suitable hydraulic parameters for Bangkok Bar sedimentation in mathematical modelling. The study covered the review of hydraulic and hydrographical conditions of Bangkok Bar and actual survey data of sedimentation rate for comparision. The study covered the sedimentation simulation in the area of the Chao Phraya River mouth of 16 x 20 square kilometers and included the calculations of flow, wave transformation, sedimentation in the steady state and considered only the sediments transported from river and by wave. The results indicated that the net river discharge tends to flow in the southeast direction where the current in the Bar is strong at the beginning of the river mouth and decreases in the direction of the Bar up to the curved portion (km. 5 - 6) of the Bar. The average wave condition in the Bar is gentle by which the wave passes through the Bar and breaks near the shoreline. Sediment diffuses from the river mouth through the curved portion of the Bar and front there, the concentration abruptly decreases in the Bar direction till deep water offshore zone. In the study, the hydraulic parameters considered are the diffusion constant and settling velocity. When considered only sediment sources from river and wave and with the constant value for the whole year, the suitable values of diffusion constant and settling velocity are found to be 0.15 and 5.0 cm/sec. However, the constant settling velocity induced the differences of sedimentation rate compared with the actual data in monthly basis, hence the phenomena should be considered in the unsteady state and the settling velocity value should also be considered as variable in the future study.